2014
DOI: 10.1039/c4ra11516c
|View full text |Cite
|
Sign up to set email alerts
|

Site occupancy and photoluminescence properties of Eu3+-activated Ba2ZnB2O6 phosphor

Abstract: A series of Ba 2 ZnB 2 O 6 :Eu 3+ phosphors with a red-emitting band centered at 616 nm were prepared by traditional high temperature solid-state reaction methods. The site-preferred occupancy of Eu 3+ in Ba 2 ZnB 2 O 6 and luminescence properties of Ba 2 ZnB 2 O 6 :Eu 3+ were studied combined with X-ray diffraction (XRD), photoluminescence excitation (PLE) spectra and emission (PL) spectra as well as temperature-dependent PL and decay curves. The Rietveld refinements indicate that the Eu 3+ ions prefer to occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…On the other hand, from the elemental mapping ( Fig. 6,24 Compared with other excitation peaks, the bands centered at 290 and 393 nm had stronger intensities. 20 Furthermore, the absorption bands located at about 393 and 462 nm are related to the 4f-4f electron transition of Eu 3+ ions, which coincides well with that of excitation spectra result (see Fig.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…On the other hand, from the elemental mapping ( Fig. 6,24 Compared with other excitation peaks, the bands centered at 290 and 393 nm had stronger intensities. 20 Furthermore, the absorption bands located at about 393 and 462 nm are related to the 4f-4f electron transition of Eu 3+ ions, which coincides well with that of excitation spectra result (see Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Aer that, the nonradiative (NR) process takes place (see Fig. 24,26 When the concentration of Eu 3+ ions in SrMoO 4 host lattice reached to a certain value, the distance between the neighboring Eu 3+ ions became small. Finally, the characteristic emissions of Eu 3+ ions corresponding to the D 1 / 7 F 1 , 5 D 1 / 7 F 2 , 5 D 0 / 7 F 1 , 5 D 0 / 7 F 2 , 5 D 0 / 7 F 3 , and 5 D 0 / 7 F 4 transitions are observed due to the radiative transition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, trivalent europium ion is a frequently used activator for red-emitting phosphors [21,22], because of an excellent red emission corresponding to its 5 D 0 e 7 F J (J ¼ 0, 1, 2, 3, 4) transition [23,24]. Moreover, it has been reported that the Eu 3þ / O 2À charge-transfer (CT) state could be located at a relatively low energy [25].…”
Section: Introductionmentioning
confidence: 99%